Comparative evaluation of Carp testis as an alternative to 17 α-Methyltestosterone on Tilapia sex reversal - Khanal, Nabin Babu; Shrestha, M. K.; Rai, Sunila; Bhujel, R. C. (Our Nature, 2015)
17 α-Methyltestosterone (MT) is a commonly used synthetic androgen for the all male tilapia fry production. The probable residual effect of MT on human health and environment has been a concern. Two trials for two seasons were conducted to evaluate the effectiveness of carp testis (CT), as a source of natural androgen, on sex reversal of Nile tilapia (Oreochromis niloticus) and compare it with MT at Department of Aquaculture, Agriculture and Forestry University, Nepal,using completely randomised block deign (RCBD). Altogether 8 treatments with 4 for methyltestosterone (40 mg MT kg-1 of diet) and 4 for 75% rohu (Labeo rohita) testis. Both source of androgen were fed for 15, 18, 21 or 24 days. Treatments were replicated thrice. The result of methyltestosterone feeding for 24 days showed significantly (p<0.05) higher percentage of male (98.5±1.5) than 15 days (87.1±3.5) but was statistically similar with 18 (91.8±2.6) and 21(94.3±3.0) days feeding. Similarly percentage of male obtained with18 (84.8 ±2.1) and 21 (85.8 ±2.9) days of CT feeding were statistically similar (p>0.05) with 24 days and also with 15 days CT treatment but the result of 24 days CT feeding was significantly higher (91.4 ±1.2) than 15 days (82.5 ±2.7) of carp testis feeding. DOI: http://dx.doi.org/10.3126/on.v12i1.12251 Our Nature (2014), 12(1): 1-7